Going Beyond the Display: A Surface Technology with an Electronically Switchable Diffuser - Izadi, Shahram; Hodges, Steve; Taylor, Stuart; Rosenfeld, Dan; Villar, Nicolas; Butler, Alex; Westhues, Jonathan (ACM Symposium on User Interface Software and Technology (UIST '08), 2008)
We introduce a new type of interactive surface technology based on a switchable projection screen which can be made diffuse or clear under electronic control. The screen can be continuously toggled between these two states so quickly that the switching is imperceptible to the human eye. It is then possible to rear-project what is perceived as a stable image onto the display surface, when the screen is in fact transparent for half the time. The clear periods may be used to project a second, different image through the display onto objects held above the surface. At the same time, a camera mounted behind the screen can see out into the en-vironment. We explore some of the possibilities this type of screen technology affords, allowing surface computing interactions to extend „beyond the display‟. We present a single self-contained system that combines these off-screen interactions with more typical multi-touch and tangible surface interactions. We describe the technical challenges in realizing our system, with the aim of allowing others to experiment with these new forms of interactive surfaces.